Organizational and Informational Support for the Treatment of Patients With COVID-19 in a Multidisciplinary Emergency Hospital - S. S. Petrikov; I. A. Tyrov; A. Y. Perminov; N. S. Fomenko (Неотложная медицинская помощь, 2020)
In modern conditions of global epidemiological challenges, a systematic approach to engineering (design) and reengineering (redesign) of treatment and diagnostic processes in hospitals acquires a special role for the state healthcare system.In this case, the focus of special attention to the management of hospitals is solving a task of organizing the treatment of patients with COVID-19 in the absence of proven clinical practice and dynamically modify the corresponding information flow, as well as the need for optimization of resource support and enhance its efficiency in the face of strong growth in the number of new cases and lack of standard solutions for the reorganization of hospitals, especially of non-infectious profile.In the paradigm of the systemic approach, effective management of the treatment and diagnostic process is not possible without a deep analysis of all its elements: from the moment the patient is admitted to the hospital until the completion of the treatment process. The recency of COVID-19 and the lack of clinical practice for the treatment of these patients have predetermined the need to develop comprehensive standards of clinical processes and their automation. It is the way of organizing the process to achieve the target state of the patient that forms the requirements for infrastructure and resource provision.The article presents the experience of the N.V. Sklifosovsky Research Institute for Emergency Medicine in organizational and informational support of the process of diagnosis and treatment of patients with COVID-19.